Study on Water Quality of Some Tributaries in Palembang City - Heni Kurniawati (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2023)
The results of monitoring the water quality of Sekanak, Bendung, and Ogan river  at some point have exceeded the quality standards referring Class II Water Quality Standards in accordance with Government Regulation of Indonesian Republic Number 22 of 2021. To find out the level of water pollution and water quality in the river,  it is necessary to  calculate  the water status and water quality indeks. The purpose of study was to evaluate the water quality status and water quality index of the Sekanak, Bendung and Ogan Rivers. Calculation of water quality status used the Nemerow and Sumitomo Pollution Index method with parameters pH, DO, BOD, COD, TSS, Nitrate, Phosphate, and Fecal Coli and calculation of water quality index in accordance with the Regulation of the Ministry of Environment and Forestry of the Indonesian Republic Number 27 of 2021. The highest concentration of BOD and COD were in Sekanak river at low tide with a value of 9.51 mg/l and 41.36 mg/l. The pollution index was in the range of 0.75 to 2.47 with a meeting quality standars status up to mildly pollutants. Water quality indexs at Sekanak, Bendung and Ogan river in 2020 - 2022 were in the moderate category, except at Ogan river in 2021 was in a good category. From statistical analysis there were  correlation between BOD and COD at the Sekanak, Bendung and Ogan River and the most significant parameters on the pollution index for Sekanak and Bendung River were Phosphate and for Ogan River was BOD.